Combinations of the azaquinazoline anti-Wolbachia agent, AWZ1066S, with benzimidazole anthelmintics synergise to mediate sub-seven-day sterilising and curative efficacies in experimental models of filariasis - Hegde, Shrilakshmi; Marriott, Amy E.; Pionnier, Nicolas; Steven, Andrew; Bulman, Christina; Gunderson, Emma; Vogel, Ian; Koschel, Marianne; Ehrens, Alexandra; Lustigman, Sara; Voronin, Denis; Tricoche, Nancy; et al. (Frontiers in Microbiology, 2024)
Lymphatic filariasis and onchocerciasis are two major neglected tropical diseases which are responsible for causing severe disability in 50 million people worldwide, whilst veterinary filariasis (heartworm) is a potentially lethal parasitic infection of companion animals. There is an urgent need for safe, short-course curative (macrofilaricidal) drugs to eliminate these debilitating parasite infections. We investigated combination treatments of the novel anti-Wolbachia azaquinazoline small molecule, AWZ1066S, with benzimidazole drugs (albendazole or oxfendazole) in up to four different rodent filariasis infection models: Brugia malayi -CB.17 SCID mice, B. malayi -Mongolian gerbils, B. pahangi -Mongolian gerbils and Litomosoides sigmodontis -Mongolian gerbils. Combination treatments synergised to elicit threshold (>90%) Wolbachia depletion from female worms in 5 days of treatment, using 2-fold lower dose-exposures of AWZ1066S than monotherapy. Short-course, lowered dose AWZ1066S-albendazole combination treatments also delivered partial adulticidal activities and/or long-lasting inhibition of embryogenesis resulting in complete transmission blockade in B. pahangi and L. sigmodontis gerbil models. We determined that short-course AWZ1066Salbendazole co-treatment significantly augmented depletion of Wolbachia populations within both germline and hypodermal tissues of B. malayi female worms, and in hypodermal tissues in male worms, indicating that anti-Wolbachia synergy is not limited to targeting female embryonic tissues. Our data provides pre-clinical proof-of-concept that sub-seven day combinations of rapid-acting novel anti-Wolbachia agents with benzimidazole anthelmintics is a promising curative and transmission-blocking drug treatment strategy for filarial diseases of medical and veterinary importance.